2016
DOI: 10.4172/2161-1009.1000283
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cigarette Smoking on Serum Lipid Profile in Male Population of Udaipur

Abstract: Cigarette smoking is associated with adverse effects on lipid profile and homocysteine thus increasing risk for atherosclerosis and coronary heart disease. Smoking is a prominent risk factor for coronary artery disease, atherosclerosis and peripheral vascular disorders. This study was undertaken to evaluate serum lipid profile in chronic smokers and to compare it with healthy non-smokers, considered as controls. Serum lipid profile was measured in 300 male subjects. Out of which 150 were smokers and 150 non-sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 19 publications
2
30
0
1
Order By: Relevance
“…Accordingly, our findings may refer to a potential absorptive effect of cigarette smoking and/or moderate coffee consumption (MCC) on the negative consequences of excessive consumption of coffee as shown in the combined effect of both factors by the results of two-way ANOVA test. However, hyperlipidemic levels of LDL-C and TC have been correlated with the separate effect of HCC and cigarette smoking in humans 18,27,28 and animal models. [29][30][31][32] Nevertheless, some studies showed that caffeine has significant effects 11,23 or no effect on the lipid profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, our findings may refer to a potential absorptive effect of cigarette smoking and/or moderate coffee consumption (MCC) on the negative consequences of excessive consumption of coffee as shown in the combined effect of both factors by the results of two-way ANOVA test. However, hyperlipidemic levels of LDL-C and TC have been correlated with the separate effect of HCC and cigarette smoking in humans 18,27,28 and animal models. [29][30][31][32] Nevertheless, some studies showed that caffeine has significant effects 11,23 or no effect on the lipid profile.…”
Section: Discussionmentioning
confidence: 99%
“…47 Nicotine stimulates the secretion of catecholamines which enhances lipolysis. 28 Moreover, caffeine acts synergistically in the presence of lipolytic hormones, such as epinephrine. It was previously pointed that the effect of caffeine on adrenoceptors is dose dependent.…”
Section: Discussionmentioning
confidence: 99%
“…6 Smoking leads to decrease in oestrogen levels, which decreases HDL cholesterol concentration. 7 Smoking leads to hyperinsulinaemia, which decreases the activity of lipoprotein lipase 8 leading to increased concentration of LDL, VLDL and TGL in the serum.…”
Section: Effects Of Cigarette Smokingmentioning
confidence: 99%
“…High density protein was significant higher in non-smokers compared to smokers. 15 Shenoi AS et al did case control study on 50 smokers taken as cases and 50 non-smokers with age, weight and dietary habits matched individuals were taken as controls. On evaluation of lipid profile, it was found that total cholesterol, triglycerides, LDL were significantly higher among cases compared to controls.…”
Section: Introductionmentioning
confidence: 99%